Use of Propeller Flaps for the Reconstruction of Defects around the Ankle - Benedetti, Fernando; Kafury, Paola; Reyes-Arceo, Fabiola; Lizardo, Carmelo; Reina, Federico; Zuluaga, Mauricio (Journal of Reconstructive Microsurgery Open, 2023)
Background This article describes the clinical results of the use of propeller flaps during reconstruction of coverage defects around the ankle.Methods A retrospective study of all patients with bone and soft tissue defects around the ankle reconstruction using propeller flap between January 2021 and December 2022 was conducted. Flap survival rate and complications were the outcomes variables.Results A total of 14 reconstructions in 13 patients (mean age: 45.8 ± 16.7 years) using propeller flaps were performed in the study period. The medial malleolus was the most affected area (n = 5) and the defect size ranged from 12 to 33.7 cm2. The posterior tibial artery was used as a perforator in 11 flaps. Complications were identified in five flaps, four developed venous congestion and one case, reactivation of infection. Only one propeller flap presented complete failure associated with necrosis. Good soft tissue coverage was achieved in 13 of 14 flaps.Conclusion Propeller flaps proved to be a valid management option during reconstruction of bone and soft tissue defects around the ankle, offering adequate coverage in most cases. Adequate patient selection is important to decrease the risk of complications.
Keywords: propeller flap; complications; necrosis; ankle